2015
DOI: 10.1021/acs.jpcb.5b04202
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Hydrophilicity and Surface Chemical Composition Microphase Separation Structure of Multicomponent Silicone Hydrogels

Abstract: Three series of multicomponent silicone hydrogels were prepared by the copolymerization of two hydrophobic silicon monomers bis(trimethylsilyloxy) methylsilylpropyl glycerol methacrylate (SiMA) and tris(trimethylsiloxy) 3-methacryloxypropylsilane (TRIS) with three hydrophilic monomers. The surface hydrophilicity of the silicone hydrogels was characterized by contact angle measurements, and an interesting phenomenon was found that the silicone hydrogels made from less hydrophobic monomer SiMA possess more hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…The silicone hydrogels were prepared using the following method . The photoinitiator D‐1173 and crosslinker EGDMA were combined in a flask.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The silicone hydrogels were prepared using the following method . The photoinitiator D‐1173 and crosslinker EGDMA were combined in a flask.…”
Section: Methodsmentioning
confidence: 99%
“…A great deal of research has focused on the preparation and properties of multifunctional silicone hydrogels . Some silicone hydrogels display an obvious change in volume in response to pH and solvent stimuli which can be observed by the naked eye .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the addition of SiNPs did little to change the wettability of these lenses. The slight increase may be attributed to a small quantity of hydrophobic PDMS (from SiNPs) exposed on the surface [23]. Figure 12 shows that the FTIR spectra of HS-series lenses differed little as the contents of SiNPs increased from 0 wt% to 1.2 wt%.…”
Section: Equilibrium Water Contentmentioning
confidence: 99%
“…However, this will decrease the oxygen permeability because of hydrophilic monomers. On the other hand, a higher PDMS content will enhance oxygen permeability but reduce the water uptake ability [11,22,23]. In silicone hydrogel contact lenses, water is a main factor to restrict the oxygen permeability [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…found that the silicone phase of SiMA and TRIS was of granular and fibrous textures, respectively, and the latter contributed to the higher oxygen permeability. In another study, it was proposed that the hydrophilicity of silicone hydrogels made from silicone monomer TRIS is better than those made from SiMA, based on phase separation structure and the nature of silicone monomers. Momentive Performance Materials, a specialty silicones company, is placing tremendous efforts in the past several years to develop new generation materials for hydrogel articles to offer performance, process simplification, and comfort to customers…”
Section: Introductionmentioning
confidence: 99%